Serum and follicular fluid thyroid hormone levels and assisted reproductive technology outcomes - Yun Ying Cai; Na Lin; Lan Ping Zhong; Hui Juan Duan; Yun Hua Dong; Ze Wu; Heng Su (BMC, 2019)
Abstract Objective The objective ofthis study was to assess the association between thyroid hormone (TH) levels in follicular fluid (FF) and serum and to determine whether THs impact assisted reproductive technology (ART) outcomes. Methods This study enrolled 299 women undergoing ART. Blood samples were drawn on the day of human chorionic gonadotrophin (HCG) administrationand analysed for thyroid-stimulating hormone (TSH), thyroxine(T4), triiodothyronine(T3),free T4 (fT4),free T3(fT3), thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TGAb) levels. FF was obtained on the oocyte pick up (OPU) day and analysed forTSH, T4, T3, fT4, fT3, TPOAb, TgAb and estradiol levels. Results (1) There were significant positive correlations between serum and FF TH and thyroid autoantibody levels. Statistically significant differences were discovered in serum and FF levels of TSH (p ≤ 0.001), T4 (p ≤ 0.001), T3 (p ≤ 0.001), TPOAbs (p ≤ 0.001) and TGAbs (p = 0.021). (2) Serum T4 levels [121.9(104.8,140.8) vs 114.1(98.6,130.6) nmol/l, p = 0.026], serum fT4 levels[(19.0(17.7,21.8) vs 18.6(17.0,20.1) pmol/l, p = 0.026], serum T4/T3 ratios [62.5 (55.7, 66.2) vs 59.4 (53.4, 64.9), p = 0.029], FF fT4 levels [19.0(17.5,21.3) vs 18.1(16.8,19.9) pmol/l, p = 0.009] and FF T4/T3 ratios [52.6 (46.4, 57.3) vs 50.0 (43.7, 53.1), p = 0.004] were significantly higher in the successful pregnancy group than the implantation failure group. (3) Spearman's rank correlation analysis revealed positive associations of both the FF T4/T3 ratio and serum TSH levels with the numbers of retrieved oocytes (total or MII) and embryos (fertilized, cleavage, and good quality). Conclusions TH levels in FF are strongly correlated with those in serum on the HCG day, and THs on the HCG day may affect ART outcomes.